A dosing nomograph for cerebrospinal fluid penetration of meropenem applied by continuous infusion in patients with nosocomial ventriculitis. (July 2022) - König, Christina; Grensemann, Jörn; Czorlich, Patrick; Schlemm, Eckhard; Kluge, Stefan; Wicha, Sebastian G.
Abstract: Objectives: In difficult-to-treat infections such as nosocomial ventriculitis, meropenem exposure in the infected compartment is often uncertain but crucial for antibacterial effects. The aim of this study was to investigate the cerebrospinal fluid (CSF) penetration of meropenem in patients with nosocomial ventriculitis and to derive a nomograph to predict effective meropenem doses as a function of clinical parameters. Methods: Retrospective patient data including meropenem serum and CSF levels as well as CSF inflammation markers were analyzed using NONMEM to assess the general pharmacokinetics and CSF penetration. Monte Carlo simulations were used to evaluate different meropenem dosing regimens. Probability of target attainment (PTA) in CSF was assessed, and a nomograph to achieve a target twice the minimal inhibitory concentration (MIC) during the dosing interval (100 % f T > 2x MIC ) was developed. Results: A one-compartment model with meropenem clearance dependent on the estimated glomerular filtration rate (CKD-EPI eGFR, p < 0.001) best described meropenem serum pharmacokinetics of 51 critically ill patients. CSF penetration ratio was correlated with the amount of protein in CSF (p < 0.001), with higher CSF protein levels accounting for higher penetration ratios. Preserved renal function (CKD-EPI eGFR >50 mL/min/1.73 m 2 ) and low CSF protein levels (<500 mg/L) resulted in 80% PTA 100 % f T > 2x MIC ) for a meropenem dose of 6 g/24 h. Discussion: High interindividual variability in meropenem CSF concentration was observed in patients with nosocomial ventriculitis. A nomograph to predict the daily meropenem dose required for target attainment for a given eGFR and CSF protein count was developed.